Analysis of Pro-Environmental Behavior using the 5R method (Rethink, Reject, Reduce, Reuse, Recycle) towards Waste Management - Rasyid, Zulmeliza (Poltekkes Kemenkes Riau, 2023)
Pro-environmental waste management behavior can help reduce environmental damage or improve environmental conditions. The 5R method is rethink, reject, reduce, reuse, recycle. Preliminary data showed that 74% of the community had low knowledge of 5R, 78% had negative 5R attitudes, 55% had poor 5R actions in waste management. This research aims to determine the analysis of Pro-Environmental Behavior using the 5R method for Waste Management. This type of research is quantitative analytical cross sectional design. The research location is Rukun Tetangga.07/Rukun Warga 01 Perhentian Marpoyan Village. The population and sample are heads of families who live in RT 07/Rukun Warga 01, Perhentian Marpoyan Village, totaling 130 heads of families (Total Sampling). Questionnaire measuring tool. Computerized data processing. Univariate and bivariate data analysis (chi square test) CI 95%. The research results show that there is a relationship between pro-environmental behavior and the 5R method in waste management. Cooperation and integration of various parties, including the community, private sector and government, is needed to overcome this waste management.